Perivascular lymphocytic aggregates in hip prosthesis‐associated adverse local tissue reactions demonstrate Th1 and Th2 activity and exhausted CD8+ cell responses. Issue 12 (15th February 2021) - Eltit, Felipe; Mohammad, Nissreen; Medina, Indira; Haegert, Anne; Duncan, Clive P.; Garbuz, Donald S.; Greidanus, Nelson V.; Masri, Bassam A.; Ng, Tony L.; Wang, Rizhi; Cox, Michael E.
Abstract: Hip implants are a successful solution for osteoarthritis; however, some individuals with metal‐on‐metal (MoM) and metal‐on‐polyethylene (MoP) prosthetics develop adverse local tissue reactions (ALTRs). While MoM and MoP ALTRs are presumed to be delayed hypersensitivity reactions to corrosion products, MoM‐ and MoP‐associated ALTRs present with different histological characteristics. We compared MoM‐ and MoP‐associated ALTRs histopathology with cobalt and chromium levels in serum and synovial fluid. We analyzed the gene expression levels of leukocyte aggregates and synovial fluid chemokines/cytokines to resolve potential pathophysiologic differences. In addition, we classified ALTRs from 79 patients according to their leukocyte infiltrates as macrophage‐dominant, mixed, and lymphocyte‐dominant. Immune‐related transcript profiles from lymphocyte‐dominant MoM‐ and MoP‐associated ALTR patients with perivascular lymphocytic aggregates were similar. Cell signatures indicated predominantly macrophage, Th1 and Th2 lymphocytic infiltrate, with strong exhausted CD8 + signature, and low Th17 and B cell, relative to healthy lymph nodes. Lymphocyte‐dominant ALTR‐associated synovial fluid contained higher levels of induced protein 10 (IP‐10), interleukin‐1 receptor antagonist (IL‐1RN), IL‐8, IL‐6, IL‐16, macrophage inflammatory protein 1 (MIP‐1α), IL‐18, MCP‐2, and lower cell‐attracting chemokine levels, when compared with prosthetic revisions lacking ALTRs. In addition, the higher levels of IP‐10, IL‐8, IL‐6, MIP‐1α, and MCP‐2 were observed within the synovial fluid of the lymphocyte‐dominant ALTRs relative to the macrophage‐dominant ALTRs. Not all cytokines/chemokines were detected in the perivascular aggregate transcripts, suggesting the existence of other sources in the affected synovia. Our results support the hypothesis of common hypersensitivity pathogenesis in lymphocyte‐dominant MoM and MoP ALTRs. The exhausted lymphocyte signature indicates chronic processes and an impaired immune response, although the cause of the persistent T‐cell activation remains unclear. The cytokine/chemokine signature of lymphocyte‐dominant‐associated ATLRs may be of utility for diagnosing this more aggressive pathogenesis.